PENERAPAN METODE TOPSIS PADA SISTEM PENDUKUNG KEPUTUSAN SANTUNAN KAUM DHUAFA DI DESA BLINGOH - Gentur Wahyu Nyipto Wibowo; Zaenal Arifin; Beni Ernando; Syamsul Ma'arif; Nadia Annisa Maori (Universitas Islam Nahdlatul Ulama Jepara, 2020)
Love Alms Community is a social institution that manages humanitarian funds, alms and alms. The distribution of compensation for the poor in the Love Alms Community had previously been running but still using the manual method, data collection of prospective beneficiaries using paper media so that it takes a long time and the risk of data loss or damage and the occurrence of differences of opinion between members with one another in determining the acceptance of the impacted compensation wrong target in the distribution of compensation. So that research is conducted for the application of the Topsis method in the application of decision support systems aimed at assisting in determining who is entitled to compensation quickly and accurately. The system development method used is RAD (Rapid Application development) with UML (Unified Modeling Language) and PHP modeling notation as a programming language using the CodeIgniter framework. The results of this application can accelerate and facilitate the work of admins in managing prospective recipient data accurately, effectively, and efficiently. This application needs to be developed into the Android system and add other methods.